Cardiopoietic stem cell therapy in ischaemic heart failure: long‐term clinical outcomes. (23rd October 2020) - Bartunek, Jozef; Terzic, Andre; Davison, Beth A.; Behfar, Atta; Sanz‐Ruiz, Ricardo; Wojakowski, Wojciech; Sherman, Warren; Heyndrickx, Guy R.; Metra, Marco; Filippatos, Gerasimos S.; Waldman, Scott A.; Teerlink, John R.; et al.
Abstract: Aims: This study aims to explore long‐term clinical outcomes of cardiopoiesis‐guided stem cell therapy for ischaemic heart failure assessed in the Congestive Heart Failure Cardiopoietic Regenerative Therapy (CHART‐1) trial. Methods and results: CHART‐1 is a multinational, randomized, and double‐blind trial conducted in 39 centres in heart failure patients ( n = 315) on standard‐of‐care therapy. The 'active' group received cardiopoietic stem cells delivered intramyocardially using a retention‐enhanced catheter. The 'control' group underwent patient‐level sham procedure. Patients were followed up to 104 weeks. In the entire study population, results of the primary hierarchical composite outcome were maintained neutral at Week 52 [Mann–Whitney estimator 0.52, 95% confidence interval (CI) 0.45–0.59, P = 0.51]. Landmark analyses suggested late clinical benefit in patients with significant left ventricular enlargement receiving adequate dosing. Specifically, beyond 100 days of follow‐up, patients with left ventricular end‐diastolic volume of 200–370 mL treated with ≤19 injections of cardiopoietic stem cells showed reduced risk of death or cardiovascular hospitalization (hazard ratio 0.38, 95% CI 0.16–0.91, P = 0.031) and cardiovascular death or heart failure hospitalization (hazard ratio 0.28, 95% CI 0.09–0.94, P = 0.040). Cardiopoietic stem cell therapy was well tolerated long term with no difference in safety readouts compared with sham at 2 years. Conclusions: Longitudinal follow‐up documents that cardiopoietic stem cell therapy is overall safe, and post hoc analyses suggest benefit in an ischaemic heart failure subpopulation defined by advanced left ventricular enlargement on tolerable stem cell dosing. The long‐term clinical follow‐up thus offers guidance for future targeted trials.